Subjectivity and the Weighting of Performance Measures: Evidence from a Balanced Scorecard - Ittner, Christopher D.; Larcker, David F.; Meyer, Marshall W. (The Accounting Review, 2003)
This study examines how different types of performance measures were weighted in a subjective balanced scorecard bonus plan adopted by a major financial services firm. Drawing upon economic and psychological studies on performance evaluation and compensation criteria, we develop hypotheses regarding the weights placed on different types of measures. We find that the subjectivity in the scorecard plan allowed superiors to reduce the “balance” in bonus awards by placing most of the weight on financial measures, to incorporate factors other than the scorecard measures in performance evaluations, to change evaluation criteria from quarter to quarter, to ignore measures that were predictive of future financial performance, and to weight measures that were not predictive of desired results. This evidence suggests that psychology-based explanations may be equally or more relevant than economicsbased explanations in explaining the firm's measurement practices. The high level of subjectivity in the balanced scorecard plan led many branch managers to complain about favoritism in bonus awards and uncertainty in the criteria being used to determine rewards. The system ultimately was abandoned in favor of a formulaic bonus plan based solely on revenues.